Online reading application SI.BYRU berbasis web - Norhayati; Bayu Pratama Nugroho; Catharina Elmayantie (Computer Science and Information Technology, 2023)
This research was purposes to create an application, namely Online Reading Application SI.BY.RU. This application is expected can help and ease the English teachers and English learners to deepen their reading comprehension skill. The research design implemented is research and development while as the main goal was prototype development. This application was developed by using CMS (content management system) WordPress. The final result of the research is an Online Reading Application SI.BY.RU that has been tested by the expert by using blackbox testing method. over all, the blackbox testing result stated that this application is valid without any revision.